2017
DOI: 10.1155/2017/9756429
|View full text |Cite
|
Sign up to set email alerts
|

To Use or Not to Use Metformin in Cerebral Ischemia: A Review of the Application of Metformin in Stroke Rodents

Abstract: Ischemic strokes are major causes of death and disability. Searching for potential therapeutic strategies to prevent and treat stroke is necessary, given the increase in overall life expectancy. Epidemiological reports indicate that metformin is an oral antidiabetic medication that can reduce the incidence of ischemic events in patients with diabetes mellitus. Its mechanism of action has not been elucidated, but metformin pleiotropic effects involve actions in addition to glycemic control. AMPK activation has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 88 publications
(127 reference statements)
1
25
0
Order By: Relevance
“…Saeedi et al also demonstrated that metformin inhibited inflammatory cytokines, oxidative stress and necrosis by acetaminophen-induced hepatotoxicity in mice through hepatocytes protection and an antiinflammation and antioxidative mechanism (42). There is clear evidence that metformin can decrease cell death in cerebral ischemia (43). In recent studies metformin was able to conduct AMPK in the experimental cerebral ischemia, suppress inflammation pathways, protect cells through antioxidant pathways throw increased the level of catalase activities and glutathione (43).…”
Section: The Novel Beneficial Effectsmentioning
confidence: 99%
“…Saeedi et al also demonstrated that metformin inhibited inflammatory cytokines, oxidative stress and necrosis by acetaminophen-induced hepatotoxicity in mice through hepatocytes protection and an antiinflammation and antioxidative mechanism (42). There is clear evidence that metformin can decrease cell death in cerebral ischemia (43). In recent studies metformin was able to conduct AMPK in the experimental cerebral ischemia, suppress inflammation pathways, protect cells through antioxidant pathways throw increased the level of catalase activities and glutathione (43).…”
Section: The Novel Beneficial Effectsmentioning
confidence: 99%
“…To mention some, metformin has been widely studied for cerebral ischemia since it possesses pleiotropic activity and modulates AMPK activation [54]. In 2016, Zhang et al administered 7 mg/kg of metformin intraperitoneally to C57BL/6 mice for 7 days, before middle cerebral artery occlusion (MCAO).…”
Section: First Neuroprotective Pharmacological and Non-pharmacologicamentioning
confidence: 99%
“…However, it remains unclear whether AMPK activation using available approaches will translate into a viable treatment strategy for PD [158]. The two cardinal pathologies of PD are the degeneration of SNc DA neurons and the accumulation of αSyn aggregates in Lewy bodies.…”
Section: Ampk Activation As a Treatment Strategy For Pdmentioning
confidence: 99%